Using Social Media to Promote Democratic Transformation - Hussein, Saja Falih (International Journal of Psychosocial Rehabilitation, 2020)
Democratic transformation cannot be accomplished as required, except with the help of several factors, including fully activating the role of civil society organizations because of their profound impact on achieving democracy. Social media has turned into a platform for expressing legitimate rights and freedoms of citizens. Social media has worked to make the masses aware of the need to confront violations that impair their rights and the need to seek a transition from authoritarian regimes to democratic systems that safeguard rights and freedoms. Work on developing skills through social media by opening direct channels with officials and decision makers to form pressure groups to follow up on pending issues.